Building fuzzy approach with linearization technique for fully rough multi-objective multi-level linear fractional programming problem - Fathy, E (Iranian journal of fuzzy systems (Online), 2021)
This paper presents a suitable solution procedure to solve the fully rough multi-objective multi-level linear fractional programming (FRMMFP) problem. First, an extension of interval method is presented to deal with roughness of the stated problem. Then, an iterative technique is proposed for linearization of fractional objectives. Finally, a modification of fuzzy approach is provided in the environment of the fully rough to solve the linear model. An example is provided for understanding the solution procedure of the proposed method.